Особенности языковой ситуации в Германии - Перепечкина, С.Е. (Культура народов Причерноморья, 2003)
The aim of the suggestted article is to research the typology of the linguistic situation in Germany and to determine its differential features on the modern stage of Germany’s society development. Numerous examples and statistic data are given to explain clearly the main idea of the things said.